Representation of Goddess Ekvira Devi - Mumbai Archive Project Team (Jio Institute, 2024)
A Koli man is wearing a T-shirt with the image of Ekvira Devi. The Koli community holds Ekvira Devi in high regard and seeks her blessings for protection, prosperity, and fulfilment of wishes. A temple dedicated to Ekvira Devi is situated in Karla, near Lonavala. This temple is a significant pilgrimage site for Kolis, especially during the festival of Navratri, during which thousands of worshippers flock there to seek her blessings.